Pelibatan Organisasi Masyarakat Dalam Intelijen Keamanan Nasional - Fernando, Yudha (UI Scholars Hub, 2019)
The problem examined in this study is the role of civil society in intelligence activities for national security, while the purpose is to determine the role and form of civil society can play in intelligence activities. Theories that researchers use include theories of intelligence, national security, institutions and sociology. The research approach used in this study is a qualitative approach and the type of descriptive qualitative research using a case study model. Researchers used interview techniques, document studies and observations. Then the data is analyzed with an interactive analysis model and validated. There are two roles that can be bound by civil society in intelligence activities, namely the role of collecting information and the role of covert action. The first role is in the form of providing information and data to national security intelligence organizations, while the second role is in the form of outreach and de-radicalization activities.